Makna Hidup Bagi Pecandu Narkoba Di Rehabilitasi Narkoba Sibolangit Centre - Johanna, Petra; Purba, Flora Liharni; Tarigan, Beby Astri; Sitorus, Friyanka H.D.; Aritonang, Marsela Giovani (Psikologi Prima, 2024)
Narcotics are substances or drugs that are basically useful if used for good purposes, for example, in the treatment of certain diseases. However, the rampant abuse of narcotics can cause harm to humans. To deal with drug abuse, one of the efforts made by the government and the private sector is to establish a rehabilitation center that aims to help and empower drug addicts to get help to escape the drug trap. Sibolangit Drug Rehabilitation Center is one of the rehabilitation centers that uses spiritual principles to help residents rise from adversity. This service activity was carried out in order to provide psychological support by bringing the theme of the meaning of life to the residents at this rehabilitation center. This activity is implemented by providing material on the meaning of life, games, clinical interviews, and discussions with residents. The expected achievement in this community service activity is that it can positively affect the participants, especially the residents, by providing them with psychological support, understanding the psychoeducation of the meaning of life, and familiarity.